Beyond Climate Change Theory: What Contributes to the Adaptive Capacity of Caribbean Small Island Communities? - Jaja, Jessica (Université d'Ottawa / University of Ottawa, 2015)
The focus of this research is on identifying the determinants of local-level climate change adaptive capacity in Caribbean small island communities. A single case study approach was employed to assess retrospectively both internal and external factors that contributed to the adaptive capacity of Paget Farm, Saint Vincent and the Grenadines. The Caribbean region’s first solar-powered desalination plant was implemented in the community specifically as a climate change adaptation strategy and thus provides an ideal case for retrospective analysis. A series of semi-structured interviews with local residents and key stakeholders revealed a number of interacting social and institutional factors that contribute to community-based adaptive capacity. Further analysis of institutional factors was undertaken using Social Network Analysis, which enabled visualization and quantification of vertical and horizontal institutional integration of the networks formed during different phases of project implementation. The research extends scholarly understanding of the determinants that influence local-level climate change adaptive capacity and provides practical evidence that can assist small island communities to respond to a changing climate.
Keywords: Climate change; Adaptive capacity; Caribbean; Small island communities; Social and institutional determinants; Social Network Analysis; Temporality